Auf dem Weg zu einer europäischen Wirtschaftsverfassung für Netzinfrastrukturen: Ausgangssituation, Veränderungen und offene Fragen - Frank Bickenbach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
Since the 1980s, the European Community has become an engine for liberalization and re-regulation in the network industries of the transport, energy and telecommunications industries. This paper describes major lines of reform in European infrastructure and regulation policy. Both, changes in the substantial policies (with regard to the liberalization and regulation of network access, the establishment and development of trans- European networks and the promotion of Services of general economic interest) and accompanying changes in the allocation of powers between the European Community and its member states in the field of infrastructure and regulation policy are described. Against this backdrop some normative questions are derived, which should be answered in order to evaluate current developments.
Keywords: K23; L43; L9; 330; Netzzugang; Infrastrukturpolitik; Deregulierung; Wettbewerbspolitik; Ordnungspolitik; Institutioneller Wandel; EU-Binnenmarkt; EU-Staaten